Strategies for Strengthening Sustainable Food Security in the Islands Province: Analysis of the Influence of Rice Production Factors and Distribution Accessibility : Strategi Penguatan Ketahanan Pangan Berkelanjutan di Provinsi Kepulauan : Analisis Pengaruh Faktor Produksi Padi dan Aksesibitas Distribusi - AGUNG RIZKI PUTRA; misbahul munir; ulfa ulfa (Ekonomi dan Bisnis, 2026)
Purpose: This study examines the Food Security Index at the regency/municipal level in the Bangka Belitung Islands Province and the Riau Islands Province, focusing on the effects of harvested rice area, rice productivity, and food distribution accessibility. Design/methodology/approach: This study employs a quantitative research method, aiming to describe the food security conditions in the Bangka Belitung Islands Province and the Riau Islands Province using numerical indicators and empirical data. The data are analyzed using panel data regression analysis to examine the effects of harvested rice area, rice productivity, and distribution accessibility in both regions. Furthermore, this analysis allows for a comparison of the factors that most significantly contribute to food security vulnerability in these two provinces. Findings: The results indicate the existence of structural differences in food security between the Riau Islands Province and the Bangka Belitung Islands Province. The Riau Islands Province is highly dependent on external access, particularly inter-regional supplies and trade, whereas the Bangka Belitung Islands Province remains reliant on local production. Harvested rice area has a negative effect in both provinces, indicating that an expansion of cultivated land does not directly contribute to food security unless accompanied by improvements in productivity. Rice production exhibits markedly different effects across the two provinces. In the Riau Islands Province, rice production has a negative and statistically significant effect, while in the Bangka Belitung Islands Province it has a positive and statistically significant effect, highlighting a key structural difference between the two regions. Road accessibility does not have a statistically significant effect in either province; however, its role is relatively more pronounced in Bangka Belitung than in the Riau Islands. Overall, food security in the Riau Islands is primarily determined by external factors, such as inter-island supply chains and trade, whereas food security in Bangka Belitung is more strongly influenced by internal factors, particularly local agricultural production. Research limitations/implications: Further research is recommended to expand the study population to include archipelagic regions across Indonesia by employing spatial analysis, thereby enhancing the understanding of food security dynamics and inter-island linkages. Practical implications: The results of the study show that each region has different characteristics, whereby the Riau Islands Province has a smaller island area compared to the Bangka Belitung Islands Province. so that the Riau Islands Province is very limited in terms of rice production and rice harvest area in supporting food security. However, road access has a positive but insignificant relationship, so the government must be able to guarantee access to imports from outside the region to meet the needs of the region. Meanwhile, in the Bangka Belitung Islands Province, rice production and road accessibility have a positive correlation, meaning that the government must strengthen local production and improve road access in order to maintain food security in the region. Originality/value: this study compares two provinces, namely the Province of Bangka Belitung Islands and the Province of Riau Islands, both of which are island regions that are equally vulnerable to food price volatility, making it important to examine food security in these two regions. It also examines whether rice production, rice harvest area, and distribution accessibility can affect food security in these regions. Paper type: This article is a study to examine how the food security index in the regencies/cities of the Bangka Belitung Islands Province and the Riau Islands Province is influenced by rice harvest area, rice productivity, and distribution accessibility in these regions.